2012
DOI: 10.3389/fphar.2012.00033
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Innate Immunity and Parkinson’s Disease

Abstract: Genetic studies on PARK genes have identified dysfunction in proteasomal, lysosomal, and mitochondrial enzymes as pathogenic for Parkinson’s disease (PD). We review the role of these and similar enzymes in mediating innate immune signaling. In particular, we have identified that a number of PARK gene products as well as other enzymes have roles in innate immune signaling as well as DNA repair and regulation, ubiquitination, mitochondrial functioning, and synaptic trafficking. PD enzymatic dysfunction is likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 123 publications
(131 reference statements)
1
13
0
1
Order By: Relevance
“…It is known that patients with PD have inadequate innate immune responses, increased markers of adaptive immunity, and disruption of the blood brain barrier. 45 This makes a common underlying immunologic association between PD and melanoma plausible.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that patients with PD have inadequate innate immune responses, increased markers of adaptive immunity, and disruption of the blood brain barrier. 45 This makes a common underlying immunologic association between PD and melanoma plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Several GO terms related to immunity are also found in common in L-DOPA and L-DOPA/HFS and never found after HFS alone. Increasing evidence support the involvement of innate and adaptive immunity in PD progression [81]; altered immune system in PD might in part be linked to an immunoregulatory role of dopamine [82]. Whether the expression of LIDs might involve an abnormal immune response then deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…106109 Currently there are very few studies exploring the relationship between exercise and the immune system in individuals with PD. Yet it is well recognized that there is a strong immune component in PD 110 . Reports have shown that exercise (cycling) can increase plasma levels of the anti-inflammatory cytokine IL-10 in individuals with PD along with improved motor performance.…”
Section: Exercise and Parkinson’s Diseasementioning
confidence: 99%